Takhrij and Hadith of Agrotechnology: Agricultural Technology Studies in the Modern Era - Syahnaz Lybiani Irawan; Wahyudin Darmalaksana; Sofiya Hasani (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith regarding agricultural technology in the modern era. This research method is a qualitative type through literature study and field studies with the takhrij and sharah hadith approaches. The results and discussion of this research is that agricultural technology in the modern era is growing. The conclusion of this research is the urgency of takhrij and syarah hadith of the Prophet Muhammad regarding the study of agricultural technology in the modern era with agrotechnology analysis.